STRATEGI KOMUNIKASI KEPALA UNIT PASAR DALAM PENGELOLAAN SAMPAH DI PASAR INDUK GEDEBAGE BANDUNG - R Fajar Salim (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2019)
Head of Market Unit requires communication strategy to convey understanding so that it can be accepted and can-do synergy with all those involved in garbage management. This research used descriptive qualitative approach. Data collection techniques are done by observation, interviews, documentation, and triangulation. The results of this research that the head of the market unit carried out a communication strategy both externally and internally. Externally established cooperation with Dinas Kebersihan Kota Bandung, PD Kebersihan Kota Bandung, Dinas Lingkungan Hidup Kota Bandung, and volunteer Gerakan Bandung Disiplin. While internally the head of the market unit established synergy with the market unit office staff, traders' representatives, and casual daily workers. Although the Head of the Market Unit still acknowledges that the results of the management have not been significant, but he is optimistic to continue to educate and hopefully there will be awareness and change, especially traders in terms of garbage management.